Study of Amino Acid Composition and Basic Technological Parameters of Viburnum Fruits Harvested in Ukraine - Olga P. Khvorost (Journal of Global Pharma Technology, 2016)
In present material the study some parameters of viburnum fruits harvested in Ukraine. Generally, the research is carried out in order to increase the product range of medicines. However, the quality of viburnum opulus fruit as raw material plant in Ukraine was not regulated due to a lack of the monograph in SPhU 2.0. The feature of our research is that it is only a fragment of the complex system of pharmacognostic study of viburnum opulus fruit. In which raw materials series from the area of preparation on the territory of Ukraine are used. By means of HPLC the comparative research of component content of the free and linked allocation of amino acids of pericarp and a stone of fruits of Viburnum opulus L. is carried out. The content of free amino acids of a stone is the most various-16 connections of such nature. The largest and approximately identical content is characteristic for replaceable amino acid of proline (more that 175 µmol/kg), which is found in a free allocation in a pericarp and a stone and in the linked allocation in a pericarp. Thus, pharmacological and pharmaco-technological tests of crushed fruits of the Viburnum opulus were conducted and also the basic technological parameters were recognized. The results of this experiment will be considered and used to study the composition and development of industrial technology of drugs, which based on them.Keywords: Fruits Viburnum opulus L., Amino acids study, Pharmaco-technological investigation basic technological parameters raw materials.